PENGARUH PERAN ORANG TUA DALAM MENDUKUNG PENDIDIKAN ANAK KELAS V SD NEGERI LABUANG BAJI II KECAMATAN MAMAJANG KOTA MAKASSAR - Rahayu, Anita Sri; Aeni Rahman, Syarifah; Ashar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Influence of Parents' Roles in Supporting Children's Education in Grade V of SD Negeri Labuang Baji II, Mamajang District, Makassar City. Thesis. Primary School Teacher Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Makassar. Supervisor 1: Syarifah Aeni Rahman, Supervisor II: Ashar.This study aims to determine the influence of parents' roles on supporting children's education in grade V of SD Negeri Labuang Baji II, Mamajang District, Makassar City. This research uses a quantitative approach with a survey method and a causal associative research design. The sample consisted of 24 students, including 9 male students and 15 female students along with their parents. Data collection techniques were carried out using questionnaires and documentation. Data analysis techniques included descriptive and inferential statistical analysis, namely validity, reliability, normality, and hypothesis testing. The results showed that the role of parents was in the high category at 84.7%, while children's educational support was in the moderate category at 77.1%. The hypothesis test results indicated that there was a significant influence between parents' roles in supporting children's education with a significance value of 0.000 ≤ 0.05, so H, was accepted and Ho was rejected. The magnitude of the influence of parents' roles on children's education was 21.3%.